Could we expect new praziquantel derivatives? A meta pharmacometrics/pharmacoinformatics analysis of all antischistosomal praziquantel derivatives found in the literature. Issue 6 (3rd June 2019) - da Silva, V.B. Ribeiro; Boucherle, B.; El-Methni, J.; Hoffmann, B.; da Silva, A.L.; Fortune, A.; de Lima, M. do Carmo Alves; Thomas, A.
ABSTRACT: Praziquantel (PZQ) is the first line drug for the treatment of human Schistosoma spp. worm infections. However, it suffers from low activity towards immature stages of the worm, and its prolonged use induces resistance/tolerance. During the last 40 years, 263 PZQ analogues have been synthesized and tested against Schistosoma spp. worms, but less than 10% of them showed significant activity. Here, we propose a rationalization of the chemical space of the PZQ derivatives by a ligand-based approach. First, we constructed an in-house database with all PZQ derivatives available in the literature. This analysis shows a high heterogeneity in the data. Fortunately, all studies include PZQ as a reference, permitting the classification of compounds into three classes according to their activities. Models involving ligand-based pharmacophore and logistic regression were performed. Five physicochemical parameters were identified as the best to explain the biological activity. In the end, we proposed new PZQ derivatives with modifications at positions 1 and 7, we analysed them with our models, and we observed that they can be more active than the previously synthesized derivatives. The main goal of this work was to conduct the most valuable meta-pharmacometrics/pharmacoinformatics analysis with all Praziquantel medicinal chemistry data available in the literature.